The impact of parenting styles on prosocial behaviour among undergraduates in Malaysia - Chan, Wai Lun; Liu, Esther Xin Yu; Khor, Chee Sin (2021)
There was an increase of criminal cases in nations as pandemic has affected countries’ economy, and this caused many families living in the poverty currently. Prosocial behaviour has become especially important, where practicing prosocial behaviour among the citizens could help those people in need and reduce the negative impact brought by the pandemic towards the country and citizens. Past studies have found parenting styles as significant predictors towards general prosocial behaviour. However, relatively little attention has been given to the specific dimensions of prosocial behaviour. Hence, this study aimed to examine the impact of authoritative, authoritarian, permissive, and neglectful parenting styles on the altruistic, anonymous, public, and responsive prosocial behaviour among undergraduates in Malaysia. One hundred and forty-two undergraduates were recruited from different higher education institutions in Malaysia and completed the online questionnaires with demographic section, scale of parenting styles (SOPS), and prosocial tendencies measure- revised (PTM-R). Sampling method was purposive sampling and multiple linear regression was used as the statistical technique in this study. Authoritative, permissive, and neglectful parenting styles were found to be significant predictors of prosocial behaviour whereas authoritarian parenting style was not suggested as a significant predictor of prosocial behaviour. The findings not only contribute the new piece of research evidence on the impact of parenting styles on the specific dimensions of prosocial behaviour, but they also highlighted the importance of practicing proper parenting styles on developing ones’ prosocial behaviour. To conclude, the study extends the suggestion to include neglectful parenting style in behaviour related studies in future and provides new directions for future research related to prosocial behaviour.